ARTIFICIAL INTELLIGENCE AS AN ACCELERATOR TOWARD MAQASID AL-SHARIAH FOCUSED FINANCIAL INCLUSION: RECONSTRUCTING ISLAMIC FINANCE IN THE DIGITAL ENVIRONMENT: KECERDASAN BUATAN SEBAGAI AKSELERATOR MENUJU INKLUSI KEUANGAN YANG BERORIENTASI PADA MAQASID SYARIAH: MEREKONSTRUKSI KEUANGAN SYARIAH DALAM LINGKUNGAN DIGITAL - Stansah Patiramadhani (Universitas Wahid Hasyim Semarang, 2026)
Financial marginalization continues one of the most ongoing issues facing Muslim-majority countries, with over one billion Muslims globally without meaningful availability to formal financial facilities. This paper examines how Artificial Intelligence (AI) can serve as a accelerator for financial inclusion in Islamic economies while advancing the objectives of Maqasid al-Shariah, the higher objectives of Islamic law. Using a systematic library research methodology, this study reviews and analyzes 15 selected studies published between 2017 and 2023, drawn from peer-reviewed journals, conceptual models, and policy analyses. The findings identify five primary mechanisms through which AI advances Maqasid al-Shariah-oriented inclusion: reducing service delivery costs for underserved populations, enabling alternative data credit scoring for the unbanked, improving the precision and reach of Zakat and Qardh-Al-Hasan distribution, democratizing access to Shariah-compliant investment through robo advisors, and strengthening regulatory compliance in Islamic fintech. Nevertheless, the study also finds that Al developments these goals only under particular management conditions, including openness in algorithmic decision processes and human academic oversight for Islamic legal understanding. The paper finds that Al's inclusion possible and its disruption threats are intrinsic, and that a complete Maqasid al-Shariah approach must address both. Findings suggest for cross-disciplinary cooperation between Islamic scholars, and decision-makers to ensure that Al serves as an authentic accelerator for justice-oriented financial inclusion in the digital economy.